GAMBARAN PENGETAHUAN KESEHATAN GIGI DAN MULUT DAN PERILAKU MEROKOK SISWA KELAS XII TEKNIK MESIN SMKN 1 KATAPANG KABUPATEN BANDUNG TAHUN 2022 - Shabrina Nurunnisa; Devy Octaviana; Tri Widyastuti; Yenni Hendriani Praptiwi (Poltekkes Kemenkes Bandung, 2023)
Smoking habits are one of the triggers for the emergence of disorders of the oral cavity and its effect on aesthetics, among others, can cause tooth discoloration, thickening of the mucosa, gingivitis, and even oral cancer. The content of cigarettes in the form of tobacco, nicotine, carbon monoxide, ammonia, and other derivatives can irritate the oral cavity when consumed due to combustion. Riskesdas 2010 research data, the percentage of the age of starting smoking in Indonesia is the largest, namely at the age of 15-19 years (43.4%). These data show that most Indonesians start smoking at the age of teenagers. The purpose of this study was to determine the description of dental and oral health knowledge and smoking behavior in class XII Mechanical Engineering students at SMKN 1 Katapang, Bandung Regency in 2022. This type of research is a descriptive study with a survey approach. Sampling of this research was done by total sampling. The way this research works is by giving questionnaires to respondents. The results of this study showed that the subject was 68 students where 47 students smoked and 21 students did not smoke. And on dental and oral health knowledge, there were 10 students (14.07%), subjects who had moderate knowledge were 25 students (38.8%), and subjects who had less knowledge were 33 students (48.5%). And for the knowledge of oral health and smoking behavior as many as 26 students who smoke with less knowledge. It was concluded that smoking behavior had a low category of knowledge regarding dental and oral health.